2014
DOI: 10.9775/kvfd.2014.11088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Yeast Cell Wall Supplementation on Performance, Carcass Characteristics, Antibody Production and Histopathological Changes in Broilers

Abstract: SummaryThis study was carried out to determine the effects of dietary yeast cell wall supplementation on growth performance, carcass traits, antibody production to sheep red blood cells (SRBC) and histopathological changes in broilers. A total of 272 Ross 308 male broiler chicks aged one day were allocated into one control group and three treatment groups each containing 68 chicks. A basal diet was supplemented with 0, 1, 2 and 3 g/kg yeast cell wall (InteMos) to obtain dietary treatments. The experimental per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
(18 reference statements)
4
9
0
Order By: Relevance
“…The meta-analysis results show limited effects on the carcass and organ weight of broilers. In agreement from 52 , 62 the carcass quality shows no significant difference after administering probiotics of both lactic acid bacteria and yeast. The one factor can be caused reduced of percentage carcass are heat-stress environmental.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The meta-analysis results show limited effects on the carcass and organ weight of broilers. In agreement from 52 , 62 the carcass quality shows no significant difference after administering probiotics of both lactic acid bacteria and yeast. The one factor can be caused reduced of percentage carcass are heat-stress environmental.…”
Section: Discussionsupporting
confidence: 66%
“…Likewise, one study 62 the use of yeast as probiotic reduced abdominal fat of broiler. Reported 62 yeast help to reduce fat deposition because, modern-broiler-farming were intensive feeding ( ad-libitum ), fatter caused limb defects, and sudden death syndrome. The probiotics reported reduced fat of broiler compared without probiotic 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the use of AO in the diets of broiler chickens can have a beneficial effect reducing the liver stress. Not in agreement with our results, Yalçinkaya et al (2012) and Yalçin et al (2014) showed that serum AST and ALT were not affected by dietary supplementation of diets with mannanoligosaccharides that derived from the cell wall of yeast, and by dietary supplementation of yeast cell wall respectively. Houshmand et al (2012) found that mannanoligosaccharides were not able to influence the antibody response to Newcastle disease vaccination; moreover, Shahir et al (2014) have not found an effect of mannanoligosaccharides also on the antibody response to influenza vaccination.…”
Section: Discussionsupporting
confidence: 88%
“…Onifade et al (1999) reported better carcass yield (72.3% vs. 68.9%) in broiler fed diet containing dried yeast than control group. In contrast, Yalçin et al (2014) and Abdel-Hafeez et al (2017) reported no effect of prebiotics supplementation on carcass yield in broilers. Other carcass parameters like breast meat yield, and abdominal fat weights were not affected (P>0.05) by dietary treatments.…”
Section: Discussionmentioning
confidence: 87%